Introgresión de la resistencia al deterioro fisiológico poscosecha en yuca Introgression in cassava of the physiological postharvest deterioration resistance - Elvia Amparo Rosero Alpala; Constantino Cuambe; Chiedozie Egesi; Teresa Sánchez; Nelson Morante; Hernán Ceballos; Martín Fregene; Juan Gonzalo Morales Osorio (Acta Agronómica)
Se evaluó una población de medios hermanos (B1PD280) proveniente del cruzamiento del parental resistente al deterioro fisiológico poscosecha (DFP) CW429-1 (Manihot esculenta x M. walkerae), y ocho genotipos élite utilizados como padres recurrentes susceptibles. Se evaluaron cinco raíces por genotipo, 7 y 14 días después de la cosecha (d.d.c.) mediante una escala (0 - 100%). Los resultados mostraron reducción significativa de DFP (entre 10% y 46% en relación con los parentales recurrentes). Cincuenta y un genotipos tuvieron alto y medio nivel de resistencia (0 - 35%), 22% y 20% de ellos correspondieron a individuos sin síntomas 7 o 14 d.d.c., respectivamente. Se estableció una posible correlación entre DFP (14 d.d.c.) y escopoletina (0.523, P < 0.001) y materia seca (0.288, P < 0.001). The accelerated Physiological Postharvest Deterioration (PPD) process limits the potential of cassava crop, diminishing its palatability and commercial value within 24-72 hours after harvest. A source of genes for drastic delay of PPD was identified in an inter-specific hybrid (CW429-1) between Manihot esculenta (cultivated cassava) and Manihot walkerae. The aim in this study was to evaluate the introgression of the resistance to PPD from the donor parent CW429-1 in cassava. A half-sib (BIPD280) population from resistant parental CW429-1 and 8 elite CIAT genotypes, used as susceptible recurrent parents, was developed and evaluated. The method proposed by Wheatley et al. (1985), with some modifications was used to quantify PPD. Five roots per genotype were evaluated 7 and 14 days after harvest (DAH), following a scale (0 - 100%), other relevant traits were evaluated. Results showed significant reduction of PPD (between 10-46% of PPD in relation to the recurrent parents). About 51% of genotypes were found to have high to medium level of resistance (0-35% PPD) of which 22 and 20% genotypes correspond to individuals without PPD after 7 and 14 DAH, respectively. A positive correlation was found between PPD (14 DAH) and scopoletin (0.523, p<0.001), and with dry matter (0.288, p<0.001). These preliminary results indicated that the scheme for introgressing PPD resistance was successful, that confirm the potential of the wild cassava in the scheme of cassava breeding.